Comprehensive Review of Ecosystem Services of Community Gardens in English- and Chinese-Language Literature - Xiaoying Ding; Haotian Zhang; Xiaoxiao Fan; Xiaoyu Zhang; Xiaopeng Yue; Ping Shu (Buildings, 2025)
Community gardens are regarded as important green spaces that promote sustainable cities. Some studies have explored the ecosystem services of community gardens in different areas. However, existing studies lack a systematic review of research on community garden ecosystem services, and there is no comparative study of English- and Chinese-language literature. This paper comprehensively reviewed key English- and Chinese-language literature on the ecosystem services of community gardens from the Web of Science and CNKI and analyzed publication years, numbers, research locations, and research topics. The results showed that the number of studies in English and Chinese has increased significantly since 2015, with a consistent upward trend. Research locations are concentrated in urban areas of Europe, America, and eastern China. Both English- and Chinese-language literature focuses on “food supply (quantity)” in the provisioning services, as well as “learning and education” and “social cohesion and integration” in cultural services. The above results are related to the governance frameworks, the management systems, the climatic conditions, and the sustainable development needs of local cities and planning strategies. Given that most of the existing research focuses on the classification and mechanisms of community garden ecosystem services, it is proposed that future research deeply explore the design factors affecting community garden ecosystem services and pay attention to the links between different ecosystem services. The main findings of this review emphasize the correlation between community garden ecosystem services and contextual factors, and point out future research directions.